PERENCANAAN DAN STRATEGI KOMUNIKASI YANG TEPAT MERUPAKAN SOLUSI KOMUNIKASI YANG EFEKTIF - Melita, Yerah (Istek Widuri Jakarta, 2019)
In everyday life communication is very important and needed by every human being, because without communication humans will